Nanocontainer properties of flexible dendrimers - Ratner, M. (Functional Materials, 2008)
Monte-Carlo simulation of solvaphobic interactions of flexible dendrimers with small molecules was conducted. It was shown that universal scaling properties of such dendrimers apply also to the case of interaction with small molecules. The dependence of conformational entropy on molecule size was found. Проведено моделювання методом Монте-Карло взаємодії дендримерів з гнучкими гілками з невеликими молекулами у розчиннику. Показано, що масштабна інваріантність дендримерів має місце і в такому випадку. Знайдено залежність конфігураційної ентропії від розміру молекули. Проведено моделирование методом Монте-Карло взаимодействия дендримеров с гибкими ветвями с небольшими молекулами. Показано, что свойства масштабной инвариантности дендримеров проявляются и в этом случае. Найдена зависимость конфигурационной энтропии от размера молекулы.